Urothelial organoids originating from Cd49fhigh mouse stem cells display Notch-dependent differentiation capacity - Catarina P. Santos (Nature Portfolio, 2019)
The biology of the urothelium has been difficult to study given the lack of methods to propagate these cells. Here, the authors generate mouse urothelial organoids derived from bladder urothelial cells with high CD49f/ITGA6 and define what regulates urothelium differentiation, which is PPARγ, EGFR and Notch signalling.